2014
DOI: 10.1038/cdd.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

RIP1 maintains DNA integrity and cell proliferation by regulating PGC-1α-mediated mitochondrial oxidative phosphorylation and glycolysis

Abstract: Aerobic glycolysis or the Warburg effect contributes to cancer cell proliferation; however, how this glucose metabolism pathway is precisely regulated remains elusive. Here we show that receptor-interacting protein 1 (RIP1), a cell death and survival signaling factor, regulates mitochondrial oxidative phosphorylation and aerobic glycolysis. Loss of RIP1 in lung cancer cells suppressed peroxisome proliferator-activated receptor c coactivator-1a (PGC-1a) expression, impairing mitochondrial oxidative phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Loss of RIP1 suppresses PGC1a expression and OxPhos, resulting in accelerated glycolysis. However, excessive glycolysis decreases cellular NAD þ levels and impairs DNA repair, which activates p53-mediated cell growth inhibition (98,99). These data provide additional evidence supporting a reciprocal regulation between metabolic adaptation and wildtype p53 in cancer cell fate determination.…”
Section: Ar/pgc1a Axis In Prostate Cancersupporting
confidence: 57%
See 1 more Smart Citation
“…Loss of RIP1 suppresses PGC1a expression and OxPhos, resulting in accelerated glycolysis. However, excessive glycolysis decreases cellular NAD þ levels and impairs DNA repair, which activates p53-mediated cell growth inhibition (98,99). These data provide additional evidence supporting a reciprocal regulation between metabolic adaptation and wildtype p53 in cancer cell fate determination.…”
Section: Ar/pgc1a Axis In Prostate Cancersupporting
confidence: 57%
“…As well as the direct regulatory mechanism between PGC1a and p53, the receptor-interacting protein 1 (RIP1)/PGC1a signaling axis indirectly affects the control of p53-dependent cell proliferation (98). This signaling pathway maintains metabolic homeostasis in lung cancer cells.…”
Section: Ar/pgc1a Axis In Prostate Cancermentioning
confidence: 99%
“…NF-kB is not involved in RIP1-mediated promotion of cell proliferation in some types of cells (5,39). However, we found that NF-kB activation was critical for RIP1 to promote melanoma cell proliferation.…”
Section: Discussionmentioning
confidence: 50%
“…11 Suppression of PGC-1α by receptor-interacting protein 1 knockdown impairs mitochondrial oxidative phosphorylation and acceleration of glycolysis in cancer cell. 12 Given that mitochondrial morphology affects energy imbalance and is continuously changed through fusion and fission events, a tight coordination between mitochondrial dynamics and interorganelle interactions is crucial. The fusion protein mitofusin (Mfn) 2 has been extensively implicated in mitochondrial fusion.…”
Section: Introductionmentioning
confidence: 99%